Pengaruh Persepsi Kemudahan, Manfaat, Kepercayaan, dan Promosi terhadap Minat Masyarakat Kota Samarinda Menggunakan Layanan Online pada Pelanggan Ojek - Sudarlan Sudarlan; Marwanto Marwanto; Imeldianti Krisma (Jurnal EKSIS, 2022)
This research uses quantitative methods. Data collection techniques in this study using questionnaires, observation, and library techniques. The sample in this study were 160 respondents. Data analysis techniques that will be used in this study are Validity Test, Reliability Test, Classical Assumption Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Test, t Test, f Test, Correlation Coefficient, Coefficient of Determination, and using IBM Software SPSS Version 19. The results of this study partially the perceived convenience variable, have a significant effect on the interest of the people of Samarinda City using online motorcycle taxi services, seen from Tcount > Ttable (2,974 > 1.975) and the sig value of 0.003 < 0.05, partially the perception variable the benefits have no significant effect on the interest of the people of Samarinda City using online motorcycle taxi services, seen from Tcount < Ttable (-1,361 < 1.975) and the sig value of 0.175 > 0.05, partially trust variable, has a significant effect on people's interest in using online motorcycle taxi services, seen from Tcount > Ttable (3,331 > 1.975) and the sig value of 0.001 < 0.05, partial promotion variables have a significant effect on the interest of the people of Samarinda City using online motorcycle taxi services, seen from Tcount > Ttable (3.885 > 1.975) and a sig value of 0.000 < 0.05, simultaneously the variables of perceived convenience, perceived benefits, trust, and promotion have an effect on the interest of the people of Samarinda City using online motorcycle taxi services, as seen from Fcount > Ftable (20,484 > 2.43) and the sig value of 0.000 <0.05.